Extensão universitária para pessoas idosas no Tocantins - Lima, Rachel Bernardes de (2023)
The demographic changes presented in world statistics are increasingly perceived by contemporary societies. Actions to meet the public policies defined for this population are urgent, and the right to education cannot be neglected. Brazilian laws that declare the rights of the elderly guarantee their right to lifelong education, attributing this service to higher education institutions (HEIs) through extension activities. Parallel to this challenge, there is a change in the training itinerary that presents the universalization of extension in undergraduate courses. This thesis aims to know the extension activities (programs, projects and courses) developed for the elderly in university centers and universities in Tocantins and the perception of these participants about the activities, as a contribution to the definition of academic extension programs. A quantitative and qualitative methodology was adopted. As a methodological procedure, the research was carried out in two studies. In the first, with the adoption of a form, we sought to know the extension activities (programs, projects and courses) developed in the period from 2018 to 2022 by HEIs in Tocantins. In the second, through a questionnaire, the profile of the elderly people participating in these activities was known and their perception of the extension activities in which they participate(ram) was analyzed. A parameter of 60 years or more was adopted in the definition of an elderly person, in accordance with Brazilian legislation. The results were examined using descriptive statistics and content analysis and presented in two articles. It was found that of the 26 HEIs in the state, eight have academic autonomy, and seven participated in the research. Of these, only three developed extension activities for the elderly in the investigated period; one municipal, one state and one federal public university. Classes and workshops are the most adopted methodologies and the promotion of quality of life is the common objective among the HEIs. Regarding the profile of the elderly people investigated, frequent in extension activities in Tocantins (n=130), it was observed that the majority are female (81.54%), aged between 66 and 75 years (58.72%), widowed (43.07%), lives alone (35.39%) and completed high school (52.31%), of which 38.71% have higher education. As for the use of Information and Communication Technologies, it was shown that WhatsApp and Facebook are the most used virtual social networks, and that elderly extension workers yearn for more knowledge in this area. Learning expectations hover over personal development themes. It was concluded that the legal desire to assign the HEI the task of promoting, through university extension, lifelong education for the elderly is a viable, feasible path, with some national and international experiences as inspiration. The research also points to the need to improve undergraduate curricula, preparing students for the challenges of gerontology, in a rapidly changing demographic context. Finally, the research provokes HEIs to take a careful look at extension, ensuring the management of the knowledge produced and, being creative in the distribution of resources, allocating them to teaching and extension.